A Kinetic Model for Dissolution of Zinc Oxide Powder Obtained from Waste Alkaline Batteries in Sodium Hydroxide Solutions - Demirkiran, Nizamettin; Özdemir, Gülistan Deniz Turhan (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2019)
The determination of individual dissolution behaviors of zinc and manganese in waste alkaline battery powders is an important subject from the points of the leaching yield, design of leaching reactor, and separation and recovery steps of hydrometallurgical process. In the current study, we investigated the dissolution kinetics of zinc oxide powder. Zinc oxide was obtained from waste alkaline batteries, and sodium hydroxide solutions were used as solvent. In the experiments, the effects of solution concentration, reaction temperature, stirring speed, solid-to-liquid ratio, and particle size on the dissolution of zinc oxide were investigated. It was demonstrated that the dissolution increased with the increasing concentration, reaction temperature, and stirring speed, and with the decreasing solid-to-liquid ratio and particle size. In consequence of the kinetic analysis performed, it was found that the dissolution kinetics of zinc powder obeyed the Avrami model. Activation energy for the process was determined to be 19.42 kJ/mol. Zinc ions in the resulting solution after dissolution process was recovered in the form of hydroxy-carbonate product by precipitation method. Zinc oxide was produced by isothermal decomposition of hydroxy-carbonate product.